Business environment for SMEs : Competitive comparison of France, Germany, Italy and Spain - Cherniavska, Anna (2016)
This bachelor thesis is focused on the competitive comparison of business environment for small and medium-sized enterprises (SMEs) within 4 chosen countries, which are France, Germany, Italy and Spain. The main goal is to analyze the economic indicators and the overall business conditions in these countries, and to choose the most favorable in terms of doing business in. Theoretical part of the thesis is devoted to understanding of SMEs principles and the approach of the European Union towards these enterprises. The first practical part analyses the business environment of 4 chosen countries by using PEST analysis. And the second practical part is based on 4 external economic indicators, which are Taxation, Labor cost, Demand, and Ease of Doing Business. The analysis in this part is based on the statics method, which allows to compare each indicator separately, and to create the final ranking of these countries, according to the selected indicators. The result of the thesis shows that the most favorable country, in terms of doing business in, became Germany, which results from 2 analyses were significantly better for SMEs.